Association between total and leisure time physical activity and risk of myocardial infarction and stroke - a Swedish cohort study - Madeleine Hummel; Essi Hantikainen; Hans-Olov Adami; Weimin Ye; Rino Bellocco; Stephanie Erika Bonn; Ylva Trolle Lagerros (BMC, 2022)
Abstract Background Physical inactivity is a known risk factor for cardiovascular disease, but it is unclear if total and leisure time activity have different impact on the risk of myocardial infarction and stroke. In this cohort, we aimed to investigate the associations between both total and leisure time physical activity in detail, and the risks of myocardial infarction and stroke, both overall and for men and women separately. Methods We assessed the association between total and leisure time physical activity on the risk of myocardial infarction and stroke in a cohort of 31,580 men and women through record linkages from 1997-2016. We used Cox proportional hazards regression models to estimate hazard ratios (HR) with 95% confidence intervals (CI) based on detailed self-reported physical activity. In the adjusted analyses, we included age, sex, body mass index, level of education, cigarette smoking, alcohol consumption, diabetes, lipid disturbance and hypertension as potential confounders. Results We identified 1,621 incident cases of myocardial infarction and 1,879 of stroke. Among men, there was an inverse association between leisure time activity and myocardial infarction in the third tertile compared to the first (HR: 0.78; 95% CI: 0.62-0.98; p for trend = 0.03). We also found an inverse association between leisure time activity and stroke in the third tertile compared to the first (HR: 0.78; 95% CI: 0.61-0.99; p for trend = 0.04), while the corresponding HR for stroke among women was 0.91; 95% CI: 0.74-1.13. We found no significant association between total physical activity and MI (HR: 1.12; 95% CI: 0.93-1.34) or stroke (HR: 1.14 95% CI: 0.94-1.39) comparing the highest to the lowest tertile in men. Women in the highest tertile of total physical activity had a 22% lower risk of myocardial infarction compared to the lowest tertile (HR: 0.78; 95% CI: 0.63-0.97; p for trend = 0.02) and an 8% (95% CI: 0.87-0.98) reduced risk of myocardial infarction with each 1 METh/day increase of leisure time physical activity. Conclusion Total physical activity was inversely associated with the risk of myocardial infarction in women, while leisure time physical activity was inversely associated with the risk of myocardial infarction and stroke in men.